Optimizing Modular Machining Line Design Problem with Mixed Activation Mode of Machining Units - Belmokhtar, Sana; Dolgui, Alexandre; Delorme, Xavier; Ignatenko, Ivan (Decision Making in Manufacturing and Services, 2007)
A modular transfer line designing problem is investigated. The problem is to find the best subset of modules (machining units) from a given set and to assign them to different stations so that technological constraints and cycle upper limit are respected and the line cost is minimal. The investigated lines have a mixed activation mode for the machining units of each station, i.e. the units of each station are arranged into a series of stages such that each stage is composed of several units activated in parallel. A mixed integer program approach is proposed to model and solve the corresponding design problem. Improvements are suggested in order to reduce the model size and speed up the computations.